Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acs.jproteome.7b00024
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Serum Exosomes from Patients with Locally Advanced Pancreatic Cancer Undergoing Chemoradiotherapy

Abstract: Pancreatic cancer is the third leading cause of cancer-related death in the USA. Despite extensive research, minimal improvements in patient outcomes have been achieved. Early identification of treatment response and metastasis would be valuable to determine the appropriate therapeutic course for patients. In this work, we isolated exosomes from the serum of 10 patients with locally advanced pancreatic cancer at serial time points over a course of therapy, and quantitative analysis was performed using the iTRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 33 publications
2
97
1
Order By: Relevance
“…Taking a somewhat more selective approach to study the effects of chemotherapy on pancreatic cancer, An et al isolated serum exosomes from patients and healthy controls. Using serum volumes of 4 mL per sample and ultracentrifugation they were able to isolate yields of exosomal proteins in the order of 0.2–0.6 μg . After 4‐plex iTRAQ labeling and LC‐MS/MS with an Orbitrap Fusion they reported in the order of 700–800 proteins per sample (in total 1559 proteins were quantified), although it is notable that there was not any additional fractionation of the labeled mixtures.…”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%
“…Taking a somewhat more selective approach to study the effects of chemotherapy on pancreatic cancer, An et al isolated serum exosomes from patients and healthy controls. Using serum volumes of 4 mL per sample and ultracentrifugation they were able to isolate yields of exosomal proteins in the order of 0.2–0.6 μg . After 4‐plex iTRAQ labeling and LC‐MS/MS with an Orbitrap Fusion they reported in the order of 700–800 proteins per sample (in total 1559 proteins were quantified), although it is notable that there was not any additional fractionation of the labeled mixtures.…”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%
“…In addition to the frequently used MS‐based proteomic platforms, quantitative analysis via isobaric tags for relative and absolute quantification (iTRAQ) provides another option, as illustrated by a new study that detected approximately 700–800 EV proteins per serum sample of cancer patients, some of which are implicated in metastasis and treatment resistance . A flow field‐flow fractionation (FlFFF) approach was employed to separate urinary EVs of PCa patients, revealing the significant difference in EV sizes between these patients and healthy controls .…”
Section: Technological Advancements In Ev Isolation Content Analysismentioning
confidence: 99%
“…However, this method suffers from drawbacks such as lengthy processing time, low recovery rates and an inability to handle small sample volumes; these drawbacks are offset by ease of use and minimal need for technical expertise. Several groups have reported on the potential and clinical significance of these exosomes . For example, Marta et al used ultracentrifugation to isolate exosomes from ovarian cancer patients and showed that plasma from ovarian cancer patients contained higher levels of exosomal proteins compared to those from benign tumor patients or healthy controls .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Marta et al used ultracentrifugation to isolate exosomes from ovarian cancer patients and showed that plasma from ovarian cancer patients contained higher levels of exosomal proteins compared to those from benign tumor patients or healthy controls . Recently, An et al isolated exosomes from pancreatic cancer patients and were able to demonstrate the role of these exosomes in inducing cell migration in ex‐vivo experiments, supporting the idea that exosomes may be involved in metastasis . However, UC‐based isolation methods are unable to distinguish exosomes from other extracellular vesicles or large protein debris having similar density.…”
Section: Introductionmentioning
confidence: 99%